Peningkatan Pemahaman Konsep Pada Mata Pelajaran IPAS Materi Indonesiaku Kaya Budaya Melalui Model Project Based Learning dengan Integrasi Kearifan Budaya Lokal - Inestia, Salsabila; Wakhyudin, Husni; Fajriyah, Khusnul; Rachmawati, Yenny (Prosiding Seminar Nasional Pendidikan Profesi Guru, 2025)
The background of this research is the low level of conceptual understanding among fourth-grade students, which negatively affected their learning outcomes, as reflected in the pre-cycle average score of 56.66 and a mastery level of only 40%. This study aims to improve students’ conceptual understanding in the subject of Natural and Social Sciences (IPAS), specifically in the topic “My Culturally Rich Indonesia,” through project-based learning integrated with local cultural wisdom. This Classroom Action Research (CAR) was conducted in three phases: pre-cycle, cycle I, and cycle II. Data were collected through assessments of students’ knowledge, skills, and mastery levels. The results showed a significant improvement in students’ conceptual understanding. In cycle I, the average knowledge score increased to 72.74 with 70% mastery, and the skill score reached 15.3. In cycle II, the knowledge score rose to 82.22 with 88% mastery, and the skill score improved to 18.5. These findings indicate that project-based learning incorporating local wisdom is effective in enhancing students’ conceptual understanding in IPAS.